Historical Instruments and Contemporary Endogenous Regressors - Gregory P. Casey; Marc P. B. Klemp (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We provide a simple framework for interpreting instrumental variable regressions when there is a gap in time between the impact of the instrument and the measurement of the endogenous variable, highlighting a particular violation of the exclusion restriction that can arise in this setting. In the presence of this violation, conventional IV regressions do not consistently estimate a structural parameter of interest. Building on our framework, we develop a simple empirical method to estimate the long-run effect of the endogenous variable. We use our bias correction method to examine the role of institutions in economic development, following Acemoglu et al. (2001). We find long-run coefficients that are smaller than the coefficients from the existing literature, demonstrating the quantitative importance of our framework.
Keywords: C10; C30; O10; O40; 330; long-run economic development; instrumental variable regression